Biodiesel from Thevetia peruviana seed oil with dimethyl carbonate using as an active catalyst potassium-methoxide - Panchal, Balaji M.; Deshmukh, Sanjay A.; Sharma, Munish R. (Penerbit Universiti Kebangsaan Malaysia, 2016)
The transesterification of Thevetia peruviana seed oil with dimethyl carbonate (DMC) for preparing biodiesel has been studied using as an active catalyst potassium-methoxide (KOCH3). The effects of reaction conditions: Molar ratio of dimethyl carbonate to Thevetia peruviana seed oil, catalyst concentration, reaction time and agitation speed on dimethyl esters (DMC-Tp-BioDs) yield were investigated. The highest DMC-Tp-BioDs yield could reach 97.1% at refluxing temperature for 90 min with molar ratio of DMC-to-oil 5:1 and 2.0% w/w KOCH3 (based on oil weight). The fuel properties of the produced DMC-Tp-BioDs were compared with the ASTM D6751-02 biodiesel standard.